2010
DOI: 10.1134/s1070428010110175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of epothilones molecule fragment (15R)-C 13 -C 21 from D-mannitol

Abstract: Effi cient synthesis of an epothilone molecules fragment (15R)-C 13 -C 21 was carried out from D-mannitol through its conversion into methyl 2,3-O-cyclohexylidene-D-glycerate followed by the cyclopropanation of the ester group with ethylmagnesium bromide in the presence of titanium(IV) isopropoxide and the transformation of the obtained cyclopropanol into the corresponding 2-substituted allyl bromide. The coupling of the latter catalyzed by copper with 2-methylthiazolyl-4-magnesium bromide, the shift of a doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The authors reported that both cyclopropyl mesylates and tosylates work in this protocol, and the scope of the Lewis acid includes MgBr 2 , MgCl 2 , AlCl 3 , and TiCl 4 . This methodology has found repeated use in the early steps of several natural products syntheses, such as epothilone A, (+)-neopeltolide, neolaulimalide, amphidinolides B1, and their corresponding building blocks (Scheme b). …”
Section: Acid-mediated Ring Opening Of Cyclopropyl Alcoholsmentioning
confidence: 99%
“…The authors reported that both cyclopropyl mesylates and tosylates work in this protocol, and the scope of the Lewis acid includes MgBr 2 , MgCl 2 , AlCl 3 , and TiCl 4 . This methodology has found repeated use in the early steps of several natural products syntheses, such as epothilone A, (+)-neopeltolide, neolaulimalide, amphidinolides B1, and their corresponding building blocks (Scheme b). …”
Section: Acid-mediated Ring Opening Of Cyclopropyl Alcoholsmentioning
confidence: 99%
“…Alkenediols have been selectively monoactivated and cyclized to yield vinyl epoxides readily. A number of naturally occurring polyols have been used as starting materials for the synthesis of vinyl epoxides by this strategy, including tartrates, 36 derivatives of mannitol, 37 xylose, 38 and mannose. 39 Crotti and his group reported the preparation of cyclic vinyl epoxides from commercially available tri-O-acetyl-D-glucal 50 (Scheme 26).…”
Section: Strategy A: From Dienesmentioning
confidence: 99%
“…Subsequently, S N 2 epoxide opening by cyanide afforded cyanohydrin 603. 37 As depicted in Scheme 244, treatment of 604 with TMSCN yielded 605, the 1,2-addition product to the ketone, 251 but in the presence of an equivalent amount of cyanide nucleophile, conjugate addition to the dienone was observed, representing an addition by pathway d with respect to the vinyl epoxide (Figure 2) resulting in 606 and 607. 252 Similar to other nucleophilic additions to the β-vinyl epoxide 53a derived from D-glucal, TMSCN also added to give the syn-1,4-addition product 609 via a coordinated delivery (Scheme 245).…”
Section: Nucleophilic Openingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account broad spectrum of biological activity of arenamides and keen interest of our research team in total and formal syntheses of natural compounds from hydroxy esters [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], a novel procedure has been developed for the preparation of protected (3S,4S)-3-hydroxy-4-methyldecanoic acid 2 which is the most complex molecular fragment of macrolides 1a-1c (Scheme 1). The starting compound for the synthesis of 2 was (7S)-7-(3-bromoprop-1-en-2-yl)-5,5-dimethyl-4,6-dioxaspiro [2.5]octane (4).…”
mentioning
confidence: 99%